Metal Ion-Catalyzed Low-Temperature Curing of Urushiol-Based Polybenzoxazine - Yang, Wen; Xie, Yaofeng; Chen, Jipeng; Huang, Chunmei; Xu, Yanlian; Lin, Yucai (Frontiers in Chemistry, 2022)
In this work, urushiol-based polybenzoxazine is curing by Lewis acid (FeCl3, AlCl3 and CuCl2) at low temperature instead of high thermal curing temperature. The effect of the Lewis acid to structures and properties of the polymers is revealed. The relating urushiol-based benzoxazine monomer (BZ) was synthesized by natural urushiol, formaldehyde and n-octylamine. The monomer was reacted with Lewis acid with the molar ratio of 3:1 (Nmonomer:NMetal) at 80 ℃ to obtain films that can be cured at room temperature. The chemical structures of benzoxazine monomers were identified by fourier-transform infrared spectroscopy (FTIR) and 1H nuclear magnetic resonance spectroscopy (1H-NMR). The interaction between the metal ion and the polymers are revealed by X-Ray Photoelectron Spectroscopy (XPS) and attenuated total reflectance-FTIR (ATR-FTIR). The effect of the Lewis acid to the mechanical properties, wettability and thermal stability was investigated. The results show that the benzoxazine cured by Cu2+ has the better performance than that cured by Al3+ and Fe3+.